Getting the most from public R&D spending in times of austerity: Some insights from SIMPATIC analysis - Reinhilde Veugelers (Bruegel, 2016)
This working paper reviews the evidence on the impact of public R&D spending. The authors first look at the evidence from micro-analysis of the impact of public intervention on private R&D and innovation, with a focus on the latest results from crosscountry micro-research performed within SIMPATIC. To analyse the impact of public R&D on growth, the micro-results on private R&D investment effects are complemented with a macro-perspective. To this end, the authors look at how public R&D performs in affecting GDP growth and jobs in applied macro-models most commonly used in EU policy analysis. They focus particularly on the NEMESIS model in development within the SIMPATIC project. The authors conclude with some policy recommendations from the reviewed micro and macro SIMPATIC evidence for designing public R&D projects and programmes.
Keywords: 330; Forschungsfinanzierung; Technologiepolitik; Wirkungsanalyse; EU-Staaten